Hemoglobin color scale a diagnostic dilemma - Anand Hema; Mir Rashid; Saxena Renu (Wolters Kluwer Medknow Publications, 2009)
Hemoglobin color scale (HCS) is a commercially available test to screen anaemia in the absence of laboratory based hemoglobinometry. The present study was aimed at to compare the efficacy of HCS with Sahli′s method (SM) for haemoglobin estimation and to estimate its sensitivity and specificity with respect to auto analyzer as the gold standard. The study was conducted from November 2006 to April 2007 at the department of hematology, All India Institute of Medical Sciences, New Delhi as a project of World Health Organization. The haemoglobin level was measured by all the three methods in 401 patients attending Haematology out patient department. Consent was taken from all the patients. Sensitivity of Sahli′s method was 98.2% and specificity was 66.2%, whereas the sensitivity of HCS was 30% and specificity was 100%. Sahli′s method was found to be in good agreement with autoanalyzer (gold standard). It was thus concluded that HCS is not as efficacious, as sahil′s method for hemoglobin estimations in field.